2001
DOI: 10.1046/j.1526-100x.2001.94006.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Biomass‐C in Reclaimed Soil of the Rhineland (Germany) and the North Bohemian Lignite Mining Areas (Czech Republic): Measured and Predicted Values

Abstract: This article compares reclaimed soils in the Rhineland lignite mining area, Germany (RA) and in the north Bohemian brown coal basin, Czech Republic (NBB). Because of highly significant differences of physical and chemical characteristics (RA was characterized by lower content of sand, clay, soil organic carbon, and total nitrogen) between both analyzed areas, the content of microbial biomass carbon (CMB) differs significantly (p < 0.01): RA: 241.17 ± 96.50 μg C/g dry soil; NBB: 424.42 ± 136.23 μg C/g. Extracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…In restored coal mines in Germany, the ratio of microbial to total organic C proved to be a reliable parameter for indicating restoration success and was still decreasing even after 50 years, indicating that restoration was continuing to stabilize (Insam & Domsch 1988). A lower ratio of microbial carbon to total carbon seems to indicate ecosystem maturity and hence restoration success (Ruzek et al 2001) although relative comparisons of total organic carbon in restored and natural sites may be a simpler measure.…”
Section: Discussionmentioning
confidence: 99%
“…In restored coal mines in Germany, the ratio of microbial to total organic C proved to be a reliable parameter for indicating restoration success and was still decreasing even after 50 years, indicating that restoration was continuing to stabilize (Insam & Domsch 1988). A lower ratio of microbial carbon to total carbon seems to indicate ecosystem maturity and hence restoration success (Ruzek et al 2001) although relative comparisons of total organic carbon in restored and natural sites may be a simpler measure.…”
Section: Discussionmentioning
confidence: 99%
“…Ruzek et al . (2001) demonstrated that although there were clear relationships between time since restoration and increases in soil microbial biomass, distinctly different algorithms had to be developed for reclaimed sites in the Czech Republic and Germany.…”
Section: Trends In Disturbed and Reclaimed Sitesmentioning
confidence: 99%
“…A particularly interesting feature of their paper is the link made between soil measurements and setting policy guidelines, in particular the proposed incentive scheme resulting from this work, designed to encourage land owners and topsoil miners to use successful restoration techniques on these sites. Ruzek et al (2001) demonstrated that although there were clear relationships between time since restoration and increases in soil microbial biomass, distinctly different algorithms had to be developed for reclaimed sites in the Czech Republic and Germany. Ruzek and co-workers indicated that this was related to both organic matter content as a starting point in new reclamations and the textural characteristics of the soils reclaimed.…”
Section: Trends In Disturbed and Reclaimed Sitesmentioning
confidence: 99%
“…Many studies have demonstrated the importance of soil microbial communities for the successful establishment and growth of plants and their community development (Zak et al 1990, St. John 1993, Zak et al 1994, Klein et al 1995, Bever et al 1997, van der Heijden et al 1998, Ruzek et al 2001, Chabrerie et al 2003, Antonsen and Olsson 2005. On the other hand, changes in plant diversity, composition, and production during succession (Dzwonko andLoster 1990, Zhu et al 2009) have been found to affect the composition and diversity of soil microbial communities (Wardle et al 1997, Bardgett and Shine 1999, Broughton and Gross 2000, Chabrerie et al 2003 due to the bi-directional exchanges between aboveand belowground communities (Bever 1994).…”
Section: Introductionmentioning
confidence: 99%